TEACHERS’ PERCEPTION AND PRACTICE OF USING LITERARY TEXTS TO TEACH READING SKILLS: THE CASE OF SOME SELECTED SCHOOLS IN AKAKI KALITY SUB-CITY, ADDIS ABABA - Dibekulu, Dawit (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2022)
¬This study aimed to assess the correlation between teachers’ perception and practice in using literary texts to teach reading skills in case of Ethio-national school, School of Indiana and Seattle academy in Addis Ababa. For this study, correlation design and both quantitative and qualitative data analyses approaches were employed. The samples were 43 teachers selected using comprehensive sampling. Questionnaire, classroom observation and focus group discussion were data collection tools. Both descriptive (frequency and percentage) and inferential statistics (Pearson correlation) were used to analyze the quantitative data and thematic narration for qualitative. The findings of the study revealed that most of the respondents perceived using literary texts in teaching reading positively. In spite of their good perceptions, their practices of using literary texts in teaching reading were infrequent. The relationship between teachers’ perception and their actual practices were positively correlated but the degree of their correlation was weak. Thus, it is possible to recommend that teachers should use all literary materials included in the text to teach reading skill.